Acesso à justiça: o idoso no setor de conciliação e mediação judicial cível - Corigliano, Renata Malheiros (2009)
This research is about the aged s access to the Justice through the Conciliation or Mediation Civil Sector of the João Mendes Jr. Court. We have tried to understand the aged´s vision in relation to the Justice and the Conciliation or Mediation Civil Sector; having the specific purpose of investigating the incidence of lawsuits involving senior citizens sent to the Sector. In regard to the Conciliation and Mediation, the solution for the conflict can be obtained through an agreement between the ones involved, which are the protagonists of it. The gathering of data was obtained through direct observation of five conciliation sessions involving the aged, in the installations of the Conciliation or Mediation Sector of the João Mendes Jr. Civil Court, 21st floor, João Mendes Square, without number, downtown, São Paulo. The selection of participants was carried out in accordance to the rules of conduct from the sector. The research analysis was qualitative. Observing that all the aged involved have used the right of priority by means of lawsuits. In all cases observed, the aged citizens were the authors of action for recovery. For all the aged interviewed, it was difficult to establish Justice. In the first case, the aged woman defined justice as something good for someone that doesn´t harm the other one . In the second case, the aged woman related justice to peace. In the cases 3 and 4, the aged agreed that justice was a good thing , while Z compared justice to injustice, saying that I always look for justice . The aged interviewed in the case 5 was more formal and emphasized that Justice is a system that has the intervention of the Public Power in the solution of conflicts between people . All the aged people were attended at the Conciliation or Mediation Sector for the first time. Only one aged woman knew about it through the media, the others have been told about the Sector by the lawyer or by the writ of summons to attend the conciliation/ mediation session. The aged women interviewed in the cases 1 and 2 didn´t speak up during the conciliation session, maintaining passive posture, probably not aware of the opportunity of questioning or showing their position. The aged ones interviewed in cases 3, 4 and 5 stood up for their rights adopting very active posture during the session. In general, the service was positively evaluated by the aged interviewed, regarding the good service performed by the conciliator, or by the Civil Court in terms of facilitating the access to Justice